Bioconvective Ag-Tio2/H2o Hybrid Nanofluid Flow Under the Influence of Brownian Motion and Thermophoresis - Afsar Hossain Sarkar, Dr. Annapurna Ramakrishna Sinde, Dr. Md Tausif Sk (Mathematical Statistician and Engineering Applications, 2023)
The aim of this study is to inspect the joined effects of attractive field and mixture nanofluid on bioconvection of a Casson nanofluid stream along a growing sheet coincided with gyrotactic microorganisms. The key fractional differential conditions are decreased to a bunch of nonlinear conventional differential conditions taking an aide of some suitable similitude changes. The mathematical aftermaths are determined by considering the bvp4c capability of Matlab. The effects of attractive field boundary, Brownian movement and attractive field on non-layered speed, nanoparticle fixation, temperature and thickness of self-moving microorganisms are deciphered through diagrams and outlines. The liquid speed close to the surface and the Nusselt number is reduce with attractive field. Attractive boundary upgrades oneself moving microorganism transition however a converse outcome is seen for thermophoresis. Likewise, the difference between the current outcomes with previously visited results is as one.